2023
DOI: 10.1097/ta.0000000000003962
|View full text |Cite
|
Sign up to set email alerts
|

Automated partial resuscitative endovascular balloon occlusion of the aorta reduces blood loss and hypotension in a highly lethal porcine liver injury model

Abstract: BACKGROUND Partial and intermittent resuscitative endovascular balloon occlusion of the aorta (pREBOA and iREBOA, respectively) are lifesaving techniques designed to extend therapeutic duration, mitigate ischemia, and bridge patients to definitive hemorrhage control. We hypothesized that automated pREBOA balloon titration compared with automated iREBOA would reduce blood loss and hypotensive episodes over a 90-minute intervention phase compared with iREBOA in an uncontrolled liver hemorrhage swine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Toward this goal, we performed thromboelastography (TEG) to characterize coagulation profile changes and measured plasma biomarkers of endothelial glycocalyx injury in a highly lethal uncontrolled hemorrhage model that incorporated two different automated pREBOA strategies, namely, iREBOA and pREBOA. Our previous study on this cohort found that pigs in the iREBOA group spent significantly more time at hypotension and had increased transfusions and blood loss than pREBOA animals (28). Based on these initial results, we conducted a secondary analysis on the hemodynamic and coagulation profiles and hypothesized that pigs receiving iREBOA would exhibit a more hypercoagulopathic response than pREBOA due to the increased periods of ischemia and frequency of abrupt changes to aortic flow patterns.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Toward this goal, we performed thromboelastography (TEG) to characterize coagulation profile changes and measured plasma biomarkers of endothelial glycocalyx injury in a highly lethal uncontrolled hemorrhage model that incorporated two different automated pREBOA strategies, namely, iREBOA and pREBOA. Our previous study on this cohort found that pigs in the iREBOA group spent significantly more time at hypotension and had increased transfusions and blood loss than pREBOA animals (28). Based on these initial results, we conducted a secondary analysis on the hemodynamic and coagulation profiles and hypothesized that pigs receiving iREBOA would exhibit a more hypercoagulopathic response than pREBOA due to the increased periods of ischemia and frequency of abrupt changes to aortic flow patterns.…”
Section: Introductionmentioning
confidence: 77%
“…The iREBOA group required significantly more blood transfusions by the end of the intervention (T90), which could potentially contribute to circulating levels of HA and SDC-1 (28,42). Alternatively, both groups received the same automated balloon support and transfusion strategy during surgical hemostasis, which may explain the similar circulating endothelial glycocalyx layer levels by the end of this surgical phase (T120).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations